2012
DOI: 10.1111/j.1439-0272.2012.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concurrent chronic administration of alcohol and nicotine on rat sperm parameters

Abstract: The prevalence of cigarette and alcohol consumption is high among young adult males during the reproductive period. The current study aimed to evaluate the impact of concurrent chronic administration of nicotine and ethanol on the quality of sperm in the rat. Fifty healthy Wistar male rats were randomly divided into five groups (n = 10) and were given the following for a period of 50 days: ethanol (E), nicotine (N), ethanol and nicotine (E/N); the control group (C) and an intact (I) group. Body weight as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(41 reference statements)
4
17
0
Order By: Relevance
“…This corroborates a previous study by our laboratory, in which adult male rats were treated with 2 g/kg ethanol 25% v/v for 63 consecutive days (Siervo et al, 2015). Ezzatabadipour et al (2012) also found no change in the body weight of rats. Cicero et al (1990) demonstrated that male Wistar rats (PND 25) treated with 6% alcohol for 39 days gained weight at the same rate as the control animals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This corroborates a previous study by our laboratory, in which adult male rats were treated with 2 g/kg ethanol 25% v/v for 63 consecutive days (Siervo et al, 2015). Ezzatabadipour et al (2012) also found no change in the body weight of rats. Cicero et al (1990) demonstrated that male Wistar rats (PND 25) treated with 6% alcohol for 39 days gained weight at the same rate as the control animals.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the findings by Priya et al (2014) using Wistar pubertal rats (PND 60) during 2 months of exposure to ethanol (2 g/kg) via orogastric tube, and by Ezzatabadipour et al (2012), we also found no changes in the sperm morphology, showing that ethanol does not affect the spermatogenic process in these experimental conditions. Conversely, Oliva et al (2006) found an increase in the number of abnormal sperm (sperm with broken tails and headless) in pubertal animals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The same slides were used for the morphology assessment. Any sperm with the head, midpiece, and tail anomaly was considered abnormal [18]. These experiments were carried out by two expert examiners blinded to the design of the study, as described elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo toxicological effects of nicotine have been assessed in many animal studies. In the male reproductive system, nicotine (0.5 mg/kg) can decrease sperm motility and count as well as increase the percentage of sperm abnormalities in rats (Oyeyipo et al 2011, Ezzatabadipour et al 2012. A more comprehensive study assessed testicular gametogenesis, steroidogenesis and the expression of steroidogenic acute regulatory proteins in nicotine-treated rats.…”
Section: Introductionmentioning
confidence: 99%